Strategi Guru dalam Pembentukan Karakter Peduli Lingkungan Bagi Siswa - SAPRIADI sapriadi; Siti Hajaroh (JURNAL PENELITIAN KEISLAMAN, 2019)
This study aims to discuss the teacher's strategy in the character building of environmental care for students in Madrasah Ibtidaiyyah Negeri (MIN: State Islamic Elementary School) 2 Lombok Tengah. This research is qualitative-descriptive research. Data collection uses observation, interview, and documentation techniques. Data sources were obtained from the principal, teachers, staff, and students. Data analysis techniques using data collection, data reduction, data display, and conclusion verification. The findings of the study include: (1) the teachers have used a very good strategy in building character for students to environmental care. The intended teacher strategies include, such as setting class assignments (picket schedule), sticking/putting up posters about cleanliness/keep clean, adding to the means of garbage disposal. The strategies that have been implemented by the teacher can make students maintain a good school/classroom environment. (2) The concern of the teachers in shaping the character of students caring for the environment in MIN 2 Lombok Tengah is seen in the form of approaching and advising students, as well as being involved in mutual cooperation activities (gotong-royong). Abstrak: penelitian ini bertujuan untuk mengetahui startegi guru dalam pembentukan karakter peduli lingkungan bagi siswa di MIN 2 Lombok Tengah. Penelitian ini merupakan penelitian kualitatif dengan pendekatan deskriptif. Pengumpulan data menggunakan teknik observasi, wawancara dan dokumentasi. Sumber data diperoleh dari kepala sekolah, guru, staf, dan siswa. Teknik analisis data menggunakan reduksi data, penyajian data, dan verifikasi pengamatan, peningkatan ketekunan dan triangulasi. Hasil temuan penelitian antara lain: (1) para guru telah menggunakan startegi yang sangat baik dalam membangun karakter bagi siswa untuk peduli lingkungan. Strategi guru yang dimaksud antara lain, seperti: penetapan jadwal piket kelas, menempelkan gambar tentang kebersihan, menambah sarana pembuangan sampah. Strategi-strategi yang telah diterapkan oleh guru dapat menjadikan siswa menjaga lingkungan sekolah/kelas dengan baik. (2) Kepedulian para guru dalam pembentukan karakter siswa peduli lingkungan di MIN 2 Lombok Tengah terlihat dalam bentuk mendekati, dan menasehati siswa, serta terlibat dalam kegiatan gotong royong.